Fragkiska Megaloudi: Plants and Diet in Greece from Neolithic to Classic Periods: the archaeobotanical remains - Dalby, Andrew (Petits Propos Culinaires, 2007)
Fragkiska Megaloudi: Plants and Diet in Greece from Neolithic to Classic Periods: the archaeobotanical remains: Archaeopress: ISBN 1841719498: 95pp.: £28.